2008
DOI: 10.2136/sssaj2007.0075
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Bulk Density of British Columbia Forest Soils from the Proctor Test: Relationships with Selected Physical and Chemical Properties

Abstract: The widespread use of heavy equipment during timber harvesting and site preparation can lead to reduced soil productivity and warrants development of new methods to assess compaction. We evaluated the effects of soil particle density, organic matter, particle size distribution, extractable oxides, and plastic and liquid limits on the maximum bulk density (MBD) of forest soils in British Columbia. Soil samples were collected from 33 sites throughout British Columbia, covering the major forest and soil types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…We showed the importance of mineral cementing agents in predicting MBD of agricultural soils, as found by Zhao et al (2008) for forest soils in British Columbia, Canada. The Si, Al, Fe and Ca oxides increased CWC but reduced MBD.…”
Section: Effects Of Mineral Cementing Agents On Compaction Indexessupporting
confidence: 55%
See 3 more Smart Citations
“…We showed the importance of mineral cementing agents in predicting MBD of agricultural soils, as found by Zhao et al (2008) for forest soils in British Columbia, Canada. The Si, Al, Fe and Ca oxides increased CWC but reduced MBD.…”
Section: Effects Of Mineral Cementing Agents On Compaction Indexessupporting
confidence: 55%
“…The Si, Al, Fe and Ca oxides increased CWC but reduced MBD. Zhao et al (2008) found that Al and Fe oxides were positively related to CWC, but were negatively related to MBD. Concentrations of Si, Mn, Al, Fe, Ca and Mg oxides are positively related to CWC as such compounds are hydrophilic (Tschapek, 1984).…”
Section: Effects Of Mineral Cementing Agents On Compaction Indexesmentioning
confidence: 89%
See 2 more Smart Citations
“…The relationship between TOC and ρ max has been identified by other authors (Díaz-Zorita and Grosso, 2000;Blanco-Canqui et al, 2009;Viana et al, 2011). Others studies have shown that the degree of humification (Zhang et al, 1997) and the levels of oxidisable organic matter (Zhao et al, 2008) contribute more to reduction of ρ max than TOC does.…”
Section: Maximum Bulk Density and Critical Water Contentmentioning
confidence: 70%